Airport Catchment Area Analysis - an Overview of Research Methods - Kujawiak , Magdalena (Studia Oeconomica Posnaniensia, 2016)
Airport catchment area is the influence area in which airport attracts its passengers. Catchment area analysis provides information that can be used in demand analysis. Data obtained through catchment area analysis are the core information for managers in the management and strategic development processes, for example, in planning new airport infrastructure. This paper aims to systematise the knowledge of catchment area studies and to present a number of study methods available to researchers with their strengths and weaknesses assessment. For this purpose, the world literature and national research on airport catchment area studies was reviewed. The analysis revealed a multitude of existing methods and tools used for determining and presenting catchment area of an airport. Each method, used properly, provides a variety of information ranging from an overview of the catchment area on the map to the data on the demand for airport services. The most beneficial, in terms of cognitive values, is to use a combination of methods based on travel time measurement and passenger preferences study.